The effects of socio-demographic characteristics, nutritional status, physical activity and physical function on cognitive function of community-dwelling older adults in the Klang Valley, Malaysia - Lim, Shiang Cheng; Gan, Wan Ying; Chan, Yoke Mun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Cognitive decline and cognitive impairment among older adults is a rising public health concern because of its association with increased risk of dementia, disability and mortality. In Malaysia, early identification of cognitive impairment is uncommon due to lack of understanding of risk profile of the elderly population. The objective of this study was to determine factors associated with cognitive impairment among community-dwelling older adults. Methods: This cross-sectional study was conducted among 698 community-dwelling older adults aged 60 years old and above in Klang Valley, Malaysia by using multi-stage sampling to determine the risk factors and predictors of cognitive impairment from a multidimensional approach. Multivariate logistic regression analysis was performed to determine the relationship between socio-demographic characteristics, physical activity, physical functional status and cognitive impairment. Results: Increased of age (OR = 1.056), being female (OR = 2.219) and Indian (OR = 2.722) were the risk factors for cognitive impairment, while years of education (OR = 0.765), physically active (OR = 0.823) and better physical function (OR = 0.843) were significantly associated with decreased risk of cognitive impairment. Marital and nutritional status failed to predict the risk of cognitive impairment. Conclusion: Given the protective effects of physical activity and physical function on the cognitive decline at later age, relevant policymakers should formulate appropriate health education programmes to promote regular physical activity to improve physical and cognitive function among Malaysians across all ages.